FasL Modulates Expression of Mmp2 in Osteoblasts - Svandova, Eva; Vesela, Barbora; Lesot, Hervé; Sadoine, Jeremy; Poliard, Anne; Matalova, Eva (Frontiers in Physiology, 2018)
FasL is a well-known actor in the apoptotic pathways but recent reports have pointed to its important novel roles beyond cell death, as observed also for bone cells. This is supported by non-apoptotic appearance of FasL during osteogenesis and by significant bone alterations unrelated to apoptosis in FasL deficient (gld) mice. The molecular mechanism behind this novel role has not yet been revealed. In this report, intramembranous bone, where osteoblasts differentiate directly from mesenchymal precursors without intermediary chondrogenic step, was investigated. Mouse mandibular bone surrounding the first lower molar was used as a model. The stage where a complex set of bone cells (osteoblasts, osteocytes, osteoclasts) is first present during development was selected for an initial examination. Immunohistochemical staining detected FasL in non-apoptotic cells at this stage. Further, FasL deficient vs. wild type samples subjected to osteogenic PCR Array analysis displayed a significantly decreased expression of Mmp2 in gld bone. To examine the possibility of this novel FasL-Mmp2 relationship, intramembranous bone-derived osteoblastic cells (MC3T3-E1) were treated with anti-FasL antibody or rmFasL. Indeed, the FasL neutralization caused a decreased expression of Mmp2 and rmFasL added to the cells resulted in the opposite effect. Since Mmp2-/- mice display age-dependent alterations in the intramembranous bone, early stages of gld mandibular bone were examined and age-dependent phenotype was was confirmed also in gld mice. Taken together, the present in vivo and in vitro findings point to a new non-apoptotic function of FasL in bone development associated with Mmp2 expression.